Acute Liver Injury with Severe Coagulopathy in Marasmus Caused by a Somatic Delusional Disorder - Lance L. Stein; Arun B. Jesudian (Case Reports in Hepatology)
Marasmus is a severe form of protein-calorie malnutrition characterized by the depletion of fat stores, muscle wasting, and the lack of edema. In developed countries, marasmus is often the result of anorexia nervosa. Abnormal transaminases with liver synthetic dysfunction have rarely been reported with anorexia nervosa. To our knowledge, we report the first detailed case of acute liver injury with severe coagulopathy (INR>1.5) in a patient with marasmus due to self-induced calorie restriction caused by a somatic delusional disorder. This case highlights the severity of liver injury that may occur with significant weight loss from self-induced calorie restriction and the rapid normalization of this injury with treatment. It is important for clinicians to be aware of patterns of acute liver injury in patients with severe protein-calorie malnutrition, regardless of the underlying cause.